TCKF-connect: A cross-disciplinary conceptual framework to investigate internationalization within the context of entrepreneurial ecosystems - Laura van Schijndel (Journal of Open Innovation: Technology, Market, and Complexity, 2019)
This conceptual paper examines the still under-researched phenomena associated with internationalization within the context of entrepreneurial ecosystems. Drawing on multiple literature streams, I develop TCKF-Connect, a cross-disciplinary conceptual framework to investigate how entrepreneurial ecosystems become globally connected, and how, in turn, an ecosystem's global connectedness can drive and sustain the internationalization processes of innovative start-ups. I propose a distinction between entrepreneurial ecosystems' connectivity and ecosystems' connectedness, where the former is purported as a necessary but not sufficient condition to achieve the latter. The framework developed revolves around the role played by a specific "vehicle" of connectivity across entrepreneurial ecosystems, i.e., temporary clusters, as conceptualized by Maskell, Bathelt and Malmberg and focuses on the role of knowledge flows within temporary clusters and across the entrepreneurial ecosystems where the temporary clusters are nested. The cross-disciplinary conceptual framework developed contributes to both research and policy debates by underpinning the investigation of research questions to further our understanding of the interplay between internationalization of entrepreneurial ecosystems and internationalization of the start-ups nested within them. The article proposes a research agenda emanating from the application of the cross-disciplinary conceptual framework developed and suggests a methodology for the empirical investigation.
Keywords: 650; clusters; temporary clusters; entrepreneurial ecosystems; start-ups; internationalization; connectedness; connectivity